The longer term outcome of children born to mothers with epilepsy. Issue 11 (15th October 2004) - Adab, N; Kini, U; Vinten, J; Ayres, J; Baker, G; Clayton-Smith, J; Coyle, H; Fryer, A; Gorry, J; Gregg, J; Mawer, G; Nicolaides, P; et al.
Abstract : Objectives: To determine the prevalence of cognitive delay and possible associated dysmorphic features in children exposed to antiepileptic drugs (AEDs) in utero. Design: Retrospective study of children born to mothers with epilepsy. Setting: Regional epilepsy clinics in Liverpool and Manchester, UK. Participants: Children aged between 6 months and 16 years born to mothers with epilepsy. Main outcome measures: Structured interviews, hospital records, clinical examination, and psychometric tests (Wechsler) were used to assess exposure and intelligence quotient (IQ). Blinded assessment of photographs was used to score children with characteristic dysmorphic features. Results: A total of 249 children aged 6 and over were studied: 41 were exposed to sodium valproate, 52 to carbamazepine, 21 to phenytoin, 49 to polytherapy, and 80 were unexposed. Mean verbal IQ was significantly lower in the valproate group compared to unexposed and other monotherapy groups. Multiple regression analysis showed that both valproate exposure and frequent tonic-clonic seizures in pregnancy were significantly associated with a lower verbal IQ despite adjusting for other confounding factors. There was a significant negative correlation between dysmorphic features and verbal IQ in children exposed to valproate. Conclusions: This study identifies valproate as a drug carrying potential risks for developmental delay and cognitive impairment and is the first to suggest that frequent tonic-clonic seizures have a similar effect. Our results need to be interpreted with caution given their retrospective nature. Women with epilepsy need careful counselling about individual risk benefit of AED treatment before pregnancy.